2022
DOI: 10.1186/s12884-022-04897-4
|View full text |Cite
|
Sign up to set email alerts
|

Translation and psychometric validation of the Arabic version of Summary of the Diabetes Self-Care Activities (SDSCA) among pregnant women with gestational diabetes

Abstract: Background and purpose There is a lack of validated tools to assess adherence to gestational diabetes (GDM) management plan among women with GDM. This study aimed to translate the Summary of Diabetes Self-Care Activity (SDSCA) into Arabic, culturally adapt it, and test its psychometric properties among women with GDM. Methods A multiphase study was used to translate and evaluate the psychometric properties of the Arabic version of SDSCA using the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…[ 17 ] which also suggested the three-factor loadings on EFA. [ 17 , 27 ] The findings vary from the previous studies done among patients with type 2 diabetes showed four factors, that is, diet, exercise, blood glucose testing, and foot care. [ 15 , 18 , 19 , 22 ] This slight difference in the subscales found between the aforesaid versions and the present study may be because of the temporary nature of GDM; the foot care is not usually included in the GDM management plan and may not apply to pregnant women with GDM.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…[ 17 ] which also suggested the three-factor loadings on EFA. [ 17 , 27 ] The findings vary from the previous studies done among patients with type 2 diabetes showed four factors, that is, diet, exercise, blood glucose testing, and foot care. [ 15 , 18 , 19 , 22 ] This slight difference in the subscales found between the aforesaid versions and the present study may be because of the temporary nature of GDM; the foot care is not usually included in the GDM management plan and may not apply to pregnant women with GDM.…”
Section: Discussionmentioning
confidence: 79%
“…Al Hashmi et al . [ 27 ] also did the psychometric evaluation of the Arabic version of SDSCA scale among pregnant women with GDM in Oman. The Arabic version of the adapted SDSCA tool revealed adequate content validity, Cronbach’s alpha of 0.74, and Pearson correlation coefficient of 0.67.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parental self-care behavior in relation to managing their children’s diabetes was assessed using the Summary of Diabetes Self-Care Activities Measure (SDSCA) [ 35 ]. This includes 10 items, using an 8-point Likert scale to gauge the frequency of specific diabetes self-care behaviors (such as diet, physical exercise, blood glucose monitoring, and foot care) over the previous 7 days.…”
Section: Methodsmentioning
confidence: 99%
“…The tool has shown good internal consistency with high inter-item correlations (0.47) and moderate test-retest reliability (0.40). However, for pregnant women with diabetes, only three areas (diet, exercise, and glucose monitoring) are evaluated because foot care and smoking are not relevant in this context [ 35 ].…”
Section: Study Phasesmentioning
confidence: 99%